Revisiting the public health implications of the United States-Mexico- Canada agreement - Tolulope Anthony Adekola (BMC, 2020)
Abstract This commentary re-examines a recent article by Labonté et al on the recent changes to two relevant provisions relating to patent rights in the final version of the United-States-Mexico-Canada Agreement (USMCA). Although the USMCA's final revised version does not add more pharmaceutical patent protection than those that already exist in the three trading partners, the agreement has done little to enhance access to generic medicines and biosimilars.